Exports of Services, Output and Productivity Growth in Europe - Bacovic, Maja (Asian Development Policy Review, 2021)
In this study, we analyse the impact of service exports on GDP and productivity growth in a sample of thirty-eight European countries for the period 2000-2019. Descriptive statistics analysis of the panel data shows that growth in exports of goods is more positively related to GDP growth, total fixed assets growth and productivity growth, while growth in export of services is more positively related to employment growth. In addition, the analysis shows that the volume of exports (in terms of its share in relation to GDP) of knowledge-intensive services (information and communication, other business services, intellectual property) is higher in more developed countries (measured as GDP per person). The pooled panel OLS model (fixed effects) with GDP growth rate and labour productivity growth as the dependent variables shows a positive impact on GDP growth of exports of services, although the positive impact of growth in exports of goods is higher. It applies to labour productivity growth, with a larger positive impact from exports of goods than services.